The millipede Craspedosoma raulinsii Leach, 1814 (Chordeumatida: Craspedosomatidae) in North America with comments on the derivation of its binomial name - Mcalpine, Donald F.; Shear, William A. (Zootaxa, 2018)
The millipede Craspedosoma raulinsii (Craspedosomatidae) is widespread in Central Europe from Belarus and southern Scandinavia west to Britain and Ireland. Although the species is often not common and rarely encountered (Blower 1985, Hoffman 1999, Lee 2006), Kime (2004) reports C. raulinsii as the third most widespread millipede in Belgium. Shelley (1990) reported C. raulinsii (as C. rawlinsii) for the first time from North America (from Gatineau Park, Quebec, Canada) and noted the occurrence is the first introduction of a representative of the order Chordeumatida in the New World. Here we report new records that suggest widespread occurrence of this introduced millipede in eastern Canada and comment on the commonly-applied spelling of the specific epithet of the species. Vouchers have been deposited in the collections of the New Brunswick Museum (NBM).